About life with humor, about jokes seriously – Three for Three by Aleksander Fredro in the context of the author’s work and biography - Rozental, Przemysław (Laughter, humour, satire, 2024)
Much can be said about Aleksander Fredro. He is a very important figure for Polish culture and art. He is commonly known as a cheerful character – considering the literary achievements of this artist in the field of comedy. Aleksander Fredro’s jokes are also known. However, the question arises whether Aleksander Fredro was joking just for the sake of a joke? The aim of the article is to present the issue of a joke in the 19th century through the prism of Aleksander Fredro’s diary Three by Three. Although the diary itself is full of jokes, it presents the difficult experiences of the author, his broken hopes regarding the Napoleonic Wars and many other events that, in the author’s opinion, left a powerful mark on him.